A study of environmental disclosures practices in Chinese energy industry - Candy Lim Chiu; Jingxin Zhang; Mingrui Li; Siyu Wei; Shengnan Xu; Xiaotong Chai (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2020)
In 2016, China increased sustainability practices among companies listed on China's stock market, making environmental regulations one of their integral policies. This states that highly polluting industries like the energy industry are required to comply with the sustainability requirements set. Concerning this event, research was conducted in 2016 to 2017, on the development of environmental disclosure (ED) practices in China and the impact of different variables on environmental disclosure index (EDI). Focusing on 150 energy companies listed on the Shanghai and Shenzhen stock exchange, the findings show that if the company had a better ROA, firm size, leverage and environmental accreditation certificate, they would like to publish more relevant environmental information.
Keywords: 650; Environmental disclosure index; Financial performance; Corporate social responsibility; Energy industry; China